Pengaruh Citra Merek dan Kualitas Produk terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Produk Skin Care Ms Glow - Ratna Ayu Nandra; Nurhadi Nurhadi (LPPM Institut Nasional Laa Roiba Bogor, 2022)
This research purposes to evaluate the influence created by brand value, product quality, and consumers complacency on consumers’ fidelity directly and indirectly thru complacency. Then the populace sample used as a reference in this subject was 100 respondents using a sampling technique, namely Purposive Sampling with the criteria of consumers aged 17 years and over and following Instagram @msglow_dee. Data analysis using Path Analysis technique (Path Analysis). The analysis results show that brand value and product quality positively and prominently affect complacency. Results show that brand value has a positive and prominent influence on consumers' fidelity. Product quality has a positive and prominent effect on consumers’ fidelity, and brand value product quality positively and prominently impacts consumers’ fidelity thru complacency. Keywords: Brand Value, Product Quality, Consumers Fidelity, Consumers Complacency.